A Highly Responsive Organic Image Sensor Based on a Two-Terminal Organic Photodetector with Photomultiplication - Wu, Yi-Lin (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.